THE CAUSATIVE AGENTS OF TINEA CRURIS - N. Moghadami; M.Emami (Tehran University of Medical Sciences, 1987)
Within a period of 8 months from February to October 1986 345 Patients with suspected clinical mycotic lesions in the region of groin were referred to the Medical Mycology Department of the School of Public Health of Tehran Medical sciences University. Out of 345 Patients, 111 (9652%) Tinea cruris, 2 cases (1.74%); Tinea cruris associated with candidiasis, 1 case (0/87%);Tinea cruris associated with Erythrasma, 1 case (0/87%); Tinea crusis associated with Tinea versicolor were Observed. Agents which were isolated contained, E. flocosum 399 cases (11.11%) new species which are intermediate between T.mentagrophytes and T. rubrun 4 cases (4.94%), M.canis 3 cases (3.71%).T.violaceum 1 case (1.23%) and 1 case (1.23%) of Chrysosporirm.